Autoeficácia do docente de medicina na utilização do OBJECTIVE STRUCTURED CLINICAL EXAMINATION (OSCE) - Bressa, Rebeca Carvalho (2018)
The belief in teacher self-efficacy (AED) is defined as the teacher's judgment of his or her abilities to achieve student engagement and learning outcomes. The Objective Structured Clinical Examination (OSCE) is a standardized tool used in the evaluation of professional performance. Associating the concepts of AED and OSCE use in the practice of the medical professor is an innovative challenge. Thus, this dissertation was constructed with three studies: the first one reviewed the national publications on OSCE and their relationship with the current context of Brazilian medical education; the second presented the main Brazilian studies on EDA and the third analyzed the associations between EDA and the OSCE application. In the first study, 32 texts were selected, of which only 18.8% described theoretical concepts about the OSCE, which means little time for experimentation of the method in Brazil. In the second, 32 articles were found, and 37.5% were aimed at investigating AED in different educational contexts, which demonstrates the concern of disseminating the construct in the academic environment. In the third one, two scales (Teacher Self-efficacy Scale - EAEP and Self-efficacy Scale - EFAE) were applied and a characterization questionnaire that, besides the socio demographic characteristics of the examined ones, presented questions directed to teacher perception about their work process and the main properties of simulated activities such as the OSCE. A total of 47 medical professors from a private university in the interior of the state of São Paulo were 55.3% male and 44.7% female, ranging in age from 31 to 78, whose teaching experience was dispersed between 1 and 35 years, with a mean of 11.5 years. In the results of the EFAE, the factors Social Persuasion and Vicarious Learning were the most endorsed, indicating that these sources are those of greater interference in the formation of the teachers' beliefs. Most of the participants had low and average scores on self-efficacy beliefs. The highest averages found were in relation to the Effectiveness factor in the Intentionality of the Action. In relation to the statistically significant correlations, these were negative and with moderate magnitudes between the factors of self-efficacy and the sources of Physiological and Affective States, indicating that the greater the belief in the capacity to teach or control the academic environment, the smaller the influences of physiological and emotional tensions in the performance and formation of these beliefs. There was only a positive correlation with weak magnitude, established between Action Intentional Efficacy and Vicarious Learning, suggesting that teachers who believe in their ability to mobilize students for the teaching-learning process may have these beliefs formed from the experiences of its formative process as a whole. The association of teachers with high levels of AED and OSCE implementation needs to be further explored, including in studies with qualitative approaches, but a priori, this hypothetical association appears to be promising in strengthening the quality of teaching.